Analisis Kompetensi Sumber Daya Manusia dan Kinerja Perajin Batik Pada Sentra Batik Pendowoharjo - Kristiana Sri Utami; Desnormasari Desnormasari (EBBANK, 2018)
Competence and performance of business actors become an important factor for small industry development effort. Business actors with high competence and performance will be better prepared to face the challenges of global crisis. This study aims to determine the influence of human resource competence (knowledge, ability, and skill) on the performance of batik crafters at batik center Pendowoharjo, Sleman Regency, Yogyakarta Special Region. This research is a descriptive research by integrating qualitative and quantitative approach. Data analysis using multiple linear regression analysis. Research respondents are 14 handmade and stamps batik crafters. The majority of craftsmen aged 41-55 years. The result of analysis shows the condition of competence of batik artisans (knowledge, ability, skill) in good category. Analysis on the performance level also shows that the majority of batik crafters (85.7%) have a good category performance. The results of regression analysis and t-test can be concluded that the competence variables that significantly influence the performance of artisans is the variable ability (ability) and skill (skill). While the variables of knowledge (knowledge) have no significant effect.